2009
DOI: 10.3109/17482960903390855
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cardiac autonomic control in patients with amyotrophic lateral sclerosis

Abstract: The aim of this study was to investigate autonomic cardiac control in patients with amyotrophic lateral sclerosis (ALS). Fifty-five patients with sporadic ALS (28 female and 27 male; average age 56.00 +/- 10.34 years) were compared to 30 healthy controls (17 female and 13 male; average age 42.87 +/- 11.91 years). Patients with previous history of cardiac disease, diabetes mellitus, and impaired respiratory function were excluded from the study. Cardiovascular autonomic tests according to Ewing, power spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 23 publications
7
50
0
2
Order By: Relevance
“…Further features of interest include creatine kinase, whose levels highly correlate with creatinine levels, suggested to be predictive of prognosis in ALS 42,43 . Pulse and blood pressure, which at first glance may be surprising predictive features for ALS, are supported by a body of literature suggesting sympathetic dysfunction in ALS [44][45][46][47] . Further research and studies are needed to assess the potential of these features and elucidate their involvement in ALS pathophysiology.…”
Section: Discussionmentioning
confidence: 64%
“…Further features of interest include creatine kinase, whose levels highly correlate with creatinine levels, suggested to be predictive of prognosis in ALS 42,43 . Pulse and blood pressure, which at first glance may be surprising predictive features for ALS, are supported by a body of literature suggesting sympathetic dysfunction in ALS [44][45][46][47] . Further research and studies are needed to assess the potential of these features and elucidate their involvement in ALS pathophysiology.…”
Section: Discussionmentioning
confidence: 64%
“…Reduced HRV and increased sympathetic tone are known to predispose to arrhythmogenesis [17,19]. They are also identified as mortality risk factors in patients with cardiac diseases and in patients with diabetic autonomic neuropathy [10]. Thus, autonomic impairment may also significantly influence disease prognosis in patients with MG and thymoma and investigations of autonomic nervous system may be of major importance in these subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Autonomic impairment has been shown to affect disease prognosis in many neurological disorders [10][11][12][13]. Therefore it merits early detection.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was little clinical information to suggest concomitant cardiovascular disease, we cannot exclude the possibility that this patient had clinically occult cardiac involvement either due to ALS or due to some other cardiovascular abnormality and she certainly had risk factors for the latter which would provide the most parsimonious explanation for the cTnT elevations [6]. However, because it has now been shown that elevations in the cTnT assay can occur due to proteins that exist in skeletal muscle after injury [7], it may be that the elevations we observed were due to ALS alone.…”
Section: Discussionmentioning
confidence: 85%